2019
DOI: 10.1057/s41307-019-00157-x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Change in Higher Education Ministries in Light of Agencification: Comparing Austria and Norway

Abstract: Reorganizing the bureaucracy is expected to improve public sector governance. In line with other policy sectors, the modernization of European higher education was characterized by such reform attempts during the past decades. The national reform agendas of most European countries in the late 1990s and early 2000s included, amongst other things, organizational changes in the ministerial bureaucracy, the establishment of public agencies in key policy areas such as quality assurance and internationalization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…One important finding of this study is that dividing areas of responsibilities between ministries and agencies is not always a zero-sum constellation (Friedrich 2019). For example, the ministry does not necessarily lose formal authority over a policy area in which an agency has gained substantial autonomy.…”
Section: Negotiating Areas Of Responsibilitymentioning
confidence: 89%
“…One important finding of this study is that dividing areas of responsibilities between ministries and agencies is not always a zero-sum constellation (Friedrich 2019). For example, the ministry does not necessarily lose formal authority over a policy area in which an agency has gained substantial autonomy.…”
Section: Negotiating Areas Of Responsibilitymentioning
confidence: 89%
“…The program as everything that someone tried to do with the hope of bringing results or influence. Thus, the program is a series of activities planned with the aim of bringing a certain result or influence [10].…”
Section: B Discussionmentioning
confidence: 99%
“…A range of recent scholarship has shown that the specific roles and responsibilities of agencies charged with quality assurance also reflect national governance traditions and the broader political-administrative systems of which they are part of (Friedrich, 2021;Jungblut & Woelert, 2018). The same can be said about agencies' organisational status -agencies can be quite tightly integrated into the state bureaucracy while others may be private enterprises or have other ownership structures which enable their operation more independently based on regulatory protections in place (Dill & Beerkens, 2010).…”
Section: The Evaluative Agenciesmentioning
confidence: 99%